PENANGANAN ORAL HIDRASI DAN KEJADIAN DEHIDRASI ANAK DIARE - Dwi Purwanti , Fera; Sumiyarini, Retno (Jurnal Media Ilmu Kesehatan, 2013)
Background: Many deaths due to diarrheal dehydration. While the primary treatment of diarrhea itself is overcome the dehydration. Rehydration therapy is highly effective for reducing mortality due to diarrheal dehydration. One factors that may affect the status of the child's diarrhea is rehidration of the parents in the treatment of oral hydration. There are 4 old men in rehydration in children with diarrhea is to provide  a liquid, but with the amount, frequency and type of fluid that is not in accordance with the fluids the body needs. Research Objectives: To determine the relationship behavior parents in handling with oral hydration with events dehydration in children with diarrhea in RSUD Saras Husada Purworejo. Research Methods: This research uses method descriptive analytical using design cross sectional. Engineering samples are used by non-probability sampling using technique Accidental Sampling. Data collection by questionnaire. The number of samples is 24 parents of children with diarrhea. Analysis of test data used was the Kendall Tau. Results: The behavior of parents in the treatment of oral hydration of children suffering from diarrhea for lack of a majority of as many as 58,3%. Dehydration status of child diarrhea with dehydration diarrhea mostly mild / moderate as many as 45,8%. Results analysis Kendall Tau of -0,443 with level a significance of 0,020. The results showed a p-value less than 0,05 (0,020 < 0,05) which means there is a relationship between behavior parents' in the treatment of oral hydration with the incidence of  dehydration in children with diarrhea in RSUD Saras Husada Purworejo. Conclusion: There is a relationship between behavior parents' in the treatment of oral hydration with the incidence of dehydration in children with diarrhea in RSUD Saras Husada Purworejo. Keywords: The oral rehidration of parents, dehydration, status dehydration.